Pengaruh Pengaruh Campuran AB Mix dengan POC Eceng Gondok terhadap Pertumbuhan dan Hasil Selada pada Hidroponik Sistem Sumbu - Agus Setiawan; Gusti Rusmayadi (Jurusan Agronomi, Fakultas Pertanian, Universitas Lambung Mangkurat, 2026)
This study entitled The Effect of Mixing AB Mix with Water Hyacinth Liquid Organic Fertilizer on the Growth and Yield of Lettuce in a Wick Hydroponic System was conducted from September to November 2025. The experiment was carried out at the Hydroponic House of the Agronomy Study Program, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Kalimantan. The experimental design used was a Completely Randomized Design (CRD) with a single factor. The factor tested was the combination of AB Mix and water hyacinth liquid organic fertilizer (LOF) with five treatment levels, namely E0 = 100% AB Mix + 0% water hyacinth LOF, E1 = 75% AB Mix + 25% water hyacinth LOF, E2 = 50% AB Mix + 50% water hyacinth LOF, E3 = 25% AB Mix + 75% water hyacinth LOF, and E4 = 0% AB Mix + 100% water hyacinth LOF. Each treatment was replicated four times, resulting in 20 experimental units. Each experimental unit consisted of six plants, giving a total of 120 plants. Parameters observed included plant height (cm), number of leaves (leaves), stem diameter (cm), leaf area (cm²), fresh weight of plants (g), fresh shoot weight (g), dry shoot weight (g), dry root weight (g), shoot–root ratio, and radiation interception fraction. The results showed that the combination of AB Mix and water hyacinth LOF had a significant effect on plant height and number of leaves at all observation periods, stem diameter at 14, 21, 28, 35, and 42 days after transplanting (DAT), and leaf area at all observation periods. This treatment also showed significant to highly significant effects on fresh plant weight, fresh shoot weight, dry shoot weight, dry root weight, shoot–root ratio, and radiation interception fraction, particularly at 28 and 42 DAT.